Material characterization of friction stir welded IS-2062 steel plate by hysteresis loop analysis - Raja A.R.; Gupta S.K.; Vashista M.; Yusufzai M.Z.K. (My University, 2025)
Present study attempts to characterize the IS-2062 of grade B steel after performing the friction stir welding. Welded steel plates have been characterized with the hysteresis loop characteristics at various magnetizing frequencies with different waveforms. Results obtained from hysteresis loop analysis were correlated with the microhardness measurement and metallographic study of welded samples. A comparison between base metal and welded sample was carried to assess the changes occurring in hysteresis loop characteristics owing to changes in mechanical properties upon friction stir welding. The grain size was observed to decrease upon friction stir welding, resulting in a greater microhardness in weld sample when compared with the base metal. Variation in magnetic hysteresis loop response like Coercivity, Permeability, Remanence and Core loss were correlating well with the grain refinement and changes in microhardness resulting from friction stir welding of steel. The study would help to establish the micro-magnetic analysis as a nondestructive technique for characterization of friction stir welded steel. © 2019 IOP Publishing Ltd.